SISTEM INFORMASI LEMBAGA PENDIDIKAN BAHASA ARAB DAN STUDI ISLAM MAâHAD ALI BIN ABI THALIB BERBASIS WEB DENGAN PHP DAN MYSQL DI UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Hidayat, Rahmat; Kusumaningsih, Rr.Yuliana Rachmawati; Sutanta, Edhy (Jurnal Script, 2014)
ABSTRACTMahad Ali Bin Abi Talib is an educational institute based at the University of Muhammadiyah Yogyakarta complexes are concentrated in Arabic and study education Keisalaman, and has been active for ten years. The problems that arise in Mahad Ali Bin Abi Talib is not the establishment of an integrated computerized system to manage the data academic faculty, courses, space, schedule, and employees that can be accessed by learners. This study develops an academic information system and an integrated digital database that can be accessed by learners. Applications developed using the software supporting OS Windows XP / 7 Ultimate 32-bit, Adobe Photoshop CS3, Xampp 1.6.4, Apache version 2, as well as PHP and MySQL.Keywords: Maâhad Ali Bin Abi Thalib, web.